Psychisches Wohlbeﬁnden im Kontext des Klimawandels unter Berücksichtigung der Arbeits- und Wohnsituation am Beispiel Eisenberg (Thüringen) - Boltersdorf, Jana; Schäfer, Susann (Raumforschung und Raumordnung, 2025)
The impact of heat events on the mental health and well-being of urban residents is the subject of this paper. Based on a combined quantitative-qualitative research design, the effects and adaptation practices are examined against the background of the individual living and working situation. The example of the Thuringian town of Eisenberg (around 11,000 inhabitants) shows that individuals are more negatively affected by heat events at work and at the same time have less scope for action there than in their own four walls. These insights underline the need to consider adaptation strategies for public employers and companies.
Published online: 3. März 2025
Gesehen am 27.03.2025